Presenting your findings: a practical guide for creating tables - Nicol, Adelheid A.; Pexman, Penny M. (Washington D.C: American Psychological Association, 2010)
Frecuency and demographic data. Means. Chi-Square. Test of means. Post hoc and a priori test of means. Correlation. Analysis of variance. Multivariate analysis of variance. Analysis of corvariance. Cluster analysisFactor analysis. Multiple regression. Logistic regression.
Incluye bibliografía